ANALISIS FRAUD PENTAGON THEORY DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD - Anisa Fahrina Amalia; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The study was conducted with aim to determine the effect of financial target, financial stability, external pressure, ineffective monitoring, nature of industry, change in auditor, audit opinion, change in director, and frequent number of CEO’s pictures against financial statement fraud in companies with largest Market Capitalization listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018. The type of study is quantitative research. The population used in the study is all companies listed on the Indonesia Stock Exchange and the sample is determined using the purposive sampling method. Based on predetermined criteria, 32 companies was obtained as the samples. The data analysis method used is multiple linear regression analysis. From the research, the results show that financial stability partially has significant effect on financial statement fraud, while financial target, external pressure, ineffective monitoring, nature of industry, change in auditor, audit opinion, change in director, and frequent number of CEO’s pictures do not affect the financial statement fraud. All variables simultaneously influence financial statement fraud with the independent variable being able to explain the dependent variable by 23.7%. Keywords: fraud pentagon theory, financial statement fraud.